ANALISIS PERAN GURU DALAM MENANGANI PERILAKU BULLYING DI SD MUHAMMADIYAH 32 MEDAN - Anggraini, Sri Devi; Fidia Tri Utari; saputri, Dilla Iksan; Nur Asdita Maharani; sitepu, Melyani Sari (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Bullying is a social behavior that often occurs in schools. Bullying can also involve students as a perpetrator and victim. Bullying behavior also has several negative impacts, both for the victim and for the perpetrator himself. If this act of bullying occurs in elementary school, then the role of a teacher is needed so that teachers are able to recognize, identify, and handle it. The purpose of this study is to find out how the role of SD Muhammadiyah 32 Medan teachers in overcoming students' bullying behavior. This research approach uses a qualitative research approach, with case study methods, interviews, and questionnaire distribution. The results of this analysis show that the role of teachers towards bullying in students is as a person who guides or gives advice and direction and fosters students so that they can overcome cases or problems that occur regarding bullying in order to minimize bullying that occurs at school. Teachers must also be able to shape students' personalities and build positive relationships with students, and teachers need to be aware of acts of violence committed by their students. For this reason, teachers play a very important role in overcoming bullying to students, so that bullying behavior does not continue until adolescence.